Door access using smart card - Foo, T.Y (University Malaysia Sarawak, (UNIMAS), 2004)
Smart Card has become the necessity in modern lifestyle. The main objective of this project is to access an electronically locked door, at the same time to create a log inside the database about the visitations done by the card users, for tracking purposes.